The impact of sexual abuse in patients undergoing colonoscopy. - Melianthe P J Nicolai; Josbert J Keller; Lieke de Vries; Andrea E van der Meulen-de Jong; Jan J Nicolai; James C H Hardwick; Hein Putter; Rob C M Pelger; Henk W Elzevier (PLoS ONE, 2014)
BACKGROUND: Sexual abuse has been linked to strong effects on gastrointestinal health. Colonoscopy can provoke intense emotional reactions in patients with a sexual abuse history and may lead to avoidance of endoscopic procedures. OBJECTIVE: To determine whether care around colonoscopy needs adjustment for patients with sexual abuse experience, thereby exploring targets for the improvement of care around colonoscopic procedures. METHODS: Questionnaires were mailed to patients (n = 1419) from two centers within 11 months after colonoscopy. Differences in experience of the colonoscopy between patients with and without a sexual abuse history were assessed and patients' views regarding physicians' inquiry about sexual abuse and care around endoscopic procedures were obtained. RESULTS: A total of 768 questionnaires were analyzed. The prevalence of sexual abuse was 3.9% in male and 9.5% in female patients. Patients born in a non-western country reported more sexual abuse (14.9%) than those born in a western country (6.3%; p = 0.008). Discomfort during colonoscopy was indicated on a scale from 0 to 10, mean distress score of patients with sexual abuse was 4.8(± 3.47) compared to 3.5(± 3.11) in patients without a sexual abuse history (p = 0.007). Abdominal pain was a predictor for higher distress during colonoscopy (β = -0.019 (SE = 0.008); p = 0.02, as well as the number of complaints indicated as reason for colonoscopy (β = 0.738 (SE = 0.276); p = 0.008). Of patients with sexual abuse experience, 53.8% believed gastroenterologists should ask about it, 43.4% said deeper sedation during colonoscopy would diminish the distress. CONCLUSIONS: Sexual abuse is prevalent in patients presenting for colonoscopy. Patients with a sexual abuse history experience more distress during the procedure and indicate that extra attention around and during colonoscopy may diminish this distress.